(untitled) (CIPEEX, 2024)
To determine the frequency of nasal septum deviation (NSD) and the anatomical variations of the nasal septum through dynamic navigation using a new cone-beam computed tomography software in a Brazilian subpopulation. Methodology: The study sample consisted of 200 cone-beam computed tomography scans of patients of both sexes. Inclusion criteria involved scans that presented the nasal septum within the field of view. The following were considered to determine nasal septum deviation in cone-beam computed tomography images: gender, age, and nasal septum deviation (presence or absence). The method for determining anatomical variations of the nasal septum in cone-beam computed tomography images included Mladina’s classification. Statistical analysis was performed using the Statistical Package for the Social Sciences software, version 20 (SPSS, Chicago, IL), with variables described as frequencies and percentages and evaluated by the chi-square test. Results: There was a predominance of female individuals and those aged between 31 and 50 years. 51.00% of the sample had a normal nasal septum. Among the population with septal deviation, 15.50% had Type III deviation, 13.50% had Type I deviation, 8.50% had Type II deviation, 4.50% had Type IV deviation, 4.0% had Type V deviation, 3.50% had Type VI deviation, and 0.50% had Type VII deviation.